Overcoming the Modern Socio-Cultural Crisis – from Postmodern to Post-Postmodern: Theoretical Aspects - Gumenyuk, Tatyana; Palchynska, Mariana; Herchanivska, Polina; Kozak, Yuriy; Kobyzhcha, Nataliia (International Journal of Criminology and Sociology, 2021)
The purpose of the article is to consider the negative aspects of postmodernism and study how post-post modernity can help humanity overcome the modern socio-cultural crisis. In their research, the authors used various scientific methods of cognition, such as analysis and synthesis, in particular meta-analysis and meta-synthesis, generalization, and induction. The authors analyze the stages of development of civilization from the point of view of social progress, highlight their main characteristics and typological differences. The considered key points characteristic of postmodern, such as pluralism, negativism, relativism, denial of binarity in thinking, the extreme degree of nihilism, etc., lead to the understanding that the crisis that arose in the political, economic, socio-cultural life of society, at the turn of 20 21 centuries, inherent in the very nature of postmodern. The values ​​and perception of the postmodern are less and less consistent with the present time, and in its depths, a new worldview begins to crystallize, conventionally called post-postmodern, as a response to overcoming the current socio-cultural crisis. Post-postmodern, postmodern, like modern before them and similar phenomena are links of one chain, interconnected with each other and logically following from the processes of previous eras. The main components of the post-postmodern, which are formed from the problems of the postmodern, are highlighted and characterized. As a result, the study showed that the currently being formed new worldview - post-postmodernity came close to the search for a new spirituality for the all-round development of a person and turning him into a socially mature being, as well as for resolving the internal contradictions of the postmodern worldview.